2019
DOI: 10.1080/21624887.2019.1644050
|View full text |Cite
|
Sign up to set email alerts
|

The gendered and racialized politics of risk analysis. The case of Frontex

Abstract: This article develops a feminist postcolonial approach to risk analysis as an increasingly central security practice in the EU's emerging border management and security regime. For this purpose, we theorize risk analysis as a sense-making practice embedded within colonial power relations. As such, risk analysis problematizes migrants and migration in gendered and racialized ways that make them amenable to border management and other, potentially violent security practices, such as detentions, returns, surveill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Racialization is understood as the process of differentiation, categorization, and meaning-making. It constructs hierarchy and differential value on the basis of perceived dichotomiesrational/irrational, civilized/barbarian, us/them, and European/non-Europeanand builds upon and reaffirms hierarchical power relations embedded within the context of (post)coloniality (Stachowitsch and Sachseder 2019). Hierarchy is constructed and relational: those who are disadvantaged by race, including Afro-descendant and Indigenous women in Colombia, are racialized as inferior, deviant, and negative, whereas those who are advantaged by race are racialized as superior, the norm, and positive.…”
Section: Notesmentioning
confidence: 94%
“…Racialization is understood as the process of differentiation, categorization, and meaning-making. It constructs hierarchy and differential value on the basis of perceived dichotomiesrational/irrational, civilized/barbarian, us/them, and European/non-Europeanand builds upon and reaffirms hierarchical power relations embedded within the context of (post)coloniality (Stachowitsch and Sachseder 2019). Hierarchy is constructed and relational: those who are disadvantaged by race, including Afro-descendant and Indigenous women in Colombia, are racialized as inferior, deviant, and negative, whereas those who are advantaged by race are racialized as superior, the norm, and positive.…”
Section: Notesmentioning
confidence: 94%
“…Although feminist research has shown how constructions of protection and security are highly gendered (Muehlenhoff, 2017;Shepherd, 2007Shepherd, , 2009Tickner, 1992), feminist analyses of the EU's refugee and asylum policies remain scarce. Stachowitsch and Sachseder (2019) demonstrate the potential of such analytical approaches: analysing how FRONTEX mobilizes gendered and racialized frames, they show how the EU agency constructs and legitimizes itself as a protector of Europe against the migrant 'other' (see also Hoijtink and Muehlenhoff, this issue). In a similar vein and in line with the rationale of this Special Issue, this article seeks to understand how gender considerations differ in EU internal and external policies.…”
Section: Building Bridges: Gender Refugee Policies and The Eu's Promotion Of Gender Normsmentioning
confidence: 99%
“…These analyses start with the use of emergency measures and securitized discourses central to early definitions of securitization (Ferreira 2018), then show how the language of crisis is not only to justify policy choices but also to flatten distinctions between migrants that might be hardworking, those that seek the social services of European states, and terrorists or criminals. Some findings suggest these securitized frames are additionally cast in gendered and racialized terms (Gray and Franck 2019;Stachowitsch and Sachseder 2019).…”
Section: Securitization: Strategic Discursive Otheringmentioning
confidence: 99%